An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G.; Pignatti, S.; Testi, a (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract The vegetation of the study site near Rome (Castelporziano Estate), where different woodland types occur, was analysed on the basis of ecological indicator values (Zeigerwerte) for light, temperature, continentality of climate, soil moisture, soil pH and nitrogen. Indicator values were estimated with Hill's reprediction algorithm for the flora of Central-Southern Italy relying on a database of 4,207 original relevés representing a balanced survey of the vegetation of this and surrounding areas. It was possible to obtain indicator values for an important fraction of the Italian Mediterranean flora. Results are ecologically reasonable, and it was possible to find strong correlation between the recalculated values and a few environmental variables. These correlations were not significant in an analogous test with subjectively derived scores of Ellenberg indicator values.
From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; Italy; reprediction algorithm; vegetation ecology

An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G.; Pignatti, S.; Testi, A. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract The vegetation of the study site near Rome (Castelporziano Estate), where different woodland types occur, was analysed on the basis of ecological indicator values (Zeigerwerte) for light, temperature, continentality of climate, soil moisture, soil pH and nitrogen. Indicator values were estimated with Hill's reprediction algorithm for the flora of Central-Southern Italy relying on a database of 4,207 original relevés representing a balanced survey of the vegetation of this and surrounding areas. It was possible to obtain indicator values for an important fraction of the Italian Mediterranean flora. Results are ecologically reasonable, and it was possible to find strong correlation between the recalculated values and a few environmental variables. These correlations were not significant in an analogous test with subjectively derived scores of Ellenberg indicator values.
From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)
Keywords: correlation; Italy; reprediction algorithm; vegetation ecology

Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V; Perrini, G; Tomasello, M (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers

Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V.; Perrini, G.; Tomasello, M. (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563doi: 10.1080/10406630213563The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers

Interannual variations of nutrient concentrations in botanical fractions from extensively managed grasslands - Ruano-Ramos, A (Animal Feed Science …, 1997)
We studied interannual variations in the concentrations of N, P, K, Ca, Mg, Na, Mn, Fe, Cu, and Zn in botanical fractions from semi-natural grassland in central-western Spain. Herbage samples were collected at the ripening stage at the end of May over a 4-year period (1987, 1988, 1989 and 1991) and classified into: grasses, legumes and forbs. There was an increase in N, P and K contents from 1987 until 1991. The interannual differences in Ca, Mn, Cu and Zn concentra- tions showed no clear trends. However, the sampling year had no significant effect on Mg and Na contents. Grasses generally exhibited significant lower nutrient contents than legumes and forbs. Forbs had N, Ca, Mg and Cu concentrations midway between those of grasses and legumes, and higher P, K, Fe and Zn contents than legumes. The P, Mg, and Na contents in the three botanical fractions were inadequate for feeding livestock. However, the K, Mn, and Fe contents in the three botanical groups and the Ca, Cu, and Zn contents in legumes and forbs were within recommended ranges for cattle. The N contents were only adequate in legumes. These and forbs appear to be most suitable for cattle feeding on account of their mineral contents
Keywords: correlation; grassland; Interannual variations; Mineral content